Construction of an Optimal Portfolio Using Sharpe's Single Index Model : A Study on Nifty Midcap 150 Scrips - Mahabub Basha, S.; Ramaratnam, M. S. (Indian Journal of Research in Capital Markets, 2017)
We made an attempt to construct an optimal portfolio using Sharpe's single index model. For this study, we collected monthly closing prices of Nifty Midcap 150 scrips from July 2011 to June 2016. In this empirical study, we considered only 25 scrips out of 150 for construction of an optimal portfolio. Nifty Midcap contains different sectors scrips. Risk can be spread among the selected scrips. Risk and return was studied for individual securities. Sharpe's single index model was formulated using the excess returns to beta ratio, cut - off rate, which finally led to the construction an optimal portfolio and determined the percentage of fund investments in various scrips. In general, investors take investment decisions based on global information and market efficiency and make portfolio choices to generate better returns. This study will fundamentally help the investors to take the right investment decisions. The present study identified an optimal portfolio from the selected 25 companies, which served to maximize the returns for the investors.